FORMAÇÃO DIDÁTICO-PEDAGÓGICA DE PROFESSORES E A DOCÊNCIA NO ENSINO SUPERIOR - Queiros, Gean Breda (2020)
This study analyzes that conceptions professor who work in higher bachelor s and undergraduate courses have about teaching and what they think about issues related to their didactic-pedagogical development. Specifically, it researches the contributions of